Pengenalan Kesenian Alat Musik Tradisional Sumatera Barat Dengan Augmented Reality Berbasis Mobile Device - Nur Anila; Muhammad Adri (UIN Sumatera Utara, 2022)
Augmented Reality (AR) is a variant of Virtual Environment (VE) or Virtual Reality (VR). AR combines the real world with the virtual world using media directly, so that three-dimensional objects created through computers can be seen in their entirety. The art of traditional musical instruments is starting to be abandoned because it tends to be more ancient, in the Minangkabau natural culture subject at SDN 01 Pi Lubang there are obstacles in introducing traditional musical instruments, namely the school does not have the facilities and infrastructure of traditional Minangkabau musical instruments. When learning the teacher only explains in the cognitive domain and uses the lecture method so that students do not experience directly the musical experience, which makes students not interested in the learning. This study aims to create a multimedia application that uses Augmented Reality technology and can provide information about traditional West Sumatran musical instruments. The Marker Based Tracking method on Augmented Reality technology is used to display three-dimensional objects on Android Smartphones. Three-dimensional objects of traditional musical instruments are designed using the Blender application. Media design uses Unity and Vuforia applications as image target or marker databases. The results obtained from the implementation of an Augmented Reality application based on a mobile device that can visualize objects of traditional West Sumatran musical instruments in three dimensions. Keywords: Information System, Service, Prototype, PHP, MySQL, Laravel